Mitos-mitos Perkawinan di Tombulu dan Inggris Suatu Analisis Kontrastif - Mamarimbing, Rolando Yoshua; Pamantung, Rina P.; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTS This study is an attempt to identify and to analyze the Wedding myths in Tombulu and England based on Barthes concept from the point of view of semiotics. This is attended to contrast the wedding forms of both tradition in the case of England and Tombulu. The aspect of this research is related to the sign system as proposed by Barthes. They are denotative and connotative. The term of signified, signifier and sign means something which is conventional and accepted by certain sign, related to what the myths. The England’s data have been collected from several book and websites, whereas the Tombulu have been taken directly from wedding event and by interviewing the informants from the Village of Wailan in District of Tomohon in regency of Minahasa. The results of research show that the wedding myths of both have a similarities in the aim of wedding function. The differences of both a myths are follows as convention wedding Myths event in England culture and the convention wedding myths in Tombulu culture. The writer hopes that this society will help student in understanding the system of wedding myths in England and Tombulu. Keyword : Myths, Wedding, Tombulu, Britain, Contrastive Analysis